Investigating The Effects Of Brand Relationship Quality On Consumer Brand Sabotage Through Mediating Effect Of Negative Emotion - Saba Qasim, Salniza Salleh , Hasnizam Shaari (International Journal of Advanced Science and Technology, 2020)
he purpose of this study is to investigate the relationship between brand relationship quality and consumer brand sabotage through mediating effect of negative emotion. This study addresses the issues regarding consumer brand sabotage. The proposed model is supported by stimulus organism response (S-O-R) theory. The theoretical framework helps future researchers to get better understanding of constructs and support to apply in other service contexts